Metabolomic differences and differential biomarkers in the meat of Jinhua pigs and Duroc×Landrace×Yorkshire pigs - Xinjie Wang; Yun Xiang; Xiaojun Zhang; Yi Xiang; Yidan Zhu; Jianhong Zhang; Lu Wang; Yanfang Liu; Huanliang Zhan (International Journal of Food Properties)
Jinhua (JH) pig, a local breed in China, is valued for its thin skin, fine bones, and tender meat. Compared to the primary commercial pig breed in China, Duroc×Landrace×Yorkshire (DLY) pigs, purebred JH pigs exhibit differences in meat characteristics, sensory parameters, and physicochemical indices. To analyze these differences between JH and DLY pork, untargeted metabolomics were employed to identify differential metabolites. 1D-myo-inositol 1,2,3,5,6-pentakisphosphate, N-acetylneuraminic acid, 6-keto-prostaglandin F1alpha, 9(S),12(S),13(S)-TriHOME, uridine-5′-diphosphate, erucic acid, keto-deoxy-nonulonic acid, phenylacetylglycine, and succinic acid were selected as biomarkers of the nonvolatile metabolome, all of which were downregulated in the JH group. Additionally, 3-octen-2-one, 4-methyl-nonane, 1-octen-3-ol, 2,3-butanediol, carvone, and benzeneacetic acid were downregulated in the JH group, except for 5-methyl-4-hexene-1-yl acetate, which was selected as a potential biomarker for the volatile differential metabolome. These biomarkers are involved in energy metabolism, lipid synthesis, stress response mechanisms, and other metabolic pathways. Flavoromics was used to annotate the differential metabolites, revealing that JH pork exhibited a lower abundance of fruity, sweet and green flavor profiles. This study provides fundamental data to enhance our understanding of the flavor and quality characteristics of JH pork and lays a foundation for the development and utilization of JH pig germplasm resources.